Penegakan Hukum Qanun Jinayat di Aceh Kaitannya dengan Pluralisme Hukum - Syaiful Mubarok (Jurnal Hukum Lex Generalis, 2025)
Aceh is a province that has several law enforcement systems in Indonesia. The pluralism of the law enforcement system in Aceh is influenced by the diversity of tribes, values ​​or Islamic religious principles. Law enforcement in Aceh is supported by the strength and recognition stipulated by the Indonesian government in Law No. 11 of 2006 concerning the Aceh Government. The Governor of Aceh ratified the qanun on October 2, 2014, which is contained in Aceh Qanun No. 6 of 2014 concerning Jinayat Law, while the main points of Islamic law are contained in Aceh Qanun No. 8 of 2014. The purpose of this study is to determine the legal pluralism in the enforcement of the qanun jinayat law in Aceh. The results of this study indicate that the enforcement of the Qanun Jinayat law in Aceh is a legal tradition that applies to the Acehnese Muslim community which is intended to provide a deterrent effect on Muslims to be more obedient to Islamic law regulations or Islamic legal principles. The Qanun Jinayat which is currently being enforced in Aceh faces challenges from both pro and con communities.